EFFECT OF EXPALNT TYPE AND SOME PLANT GROWTH REGULATORS ON CULTURE INITIATION OF STEVIA PLANTS IN VITRO - & Al-Obaidy, Khierallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted in order to study the effect of explant type and some plant growth regulators on culture initiation of Stevia rebaudiana Bertoni in vitro. The experiments included surface sterilization and test two types of explants (shoot tips and stem nodes) and the impact of KIN and BA and IAA and IBA in the cultures initiation. Results revealed the efficiency of sodium hypochlorite (NaOCl) for disinfestation of explant at 0.050% concentration giving less contamination for shoot tips and stem nods (10% and 20% respectively). Results showed that shoot tips inoculated in MS medium plus KIN at 0.3 mg. L-1 was significantly increase the number of regenerated shoots as it produced 4.2 shoots per explant while medium without cytokinin (control) produced less number of shoots reached 1.4 shoots per explant. KIN treatment reduced shoots length as control treatment produced the highest length (6.74 cm). The interaction between the explant type and BA concentration was significantly increase the number of regenerated shoots as shoot tips produced 3.6 shoots per explant in MS medium supplemented with 0.1 mg. L-1. BA treatment reduced shoots length as control treatment produced the highest length (6.74 cm). No positive effect was gain when auxins (IBA and IAA) were added in combination with cytokinin in culture medium. The above results can be adopted to established stevia in vitro culture successfully.